PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL PEMBELAJARAN IPA KELAS V SD - Rerim, Maria; ., Rosnita; ., Maridjo AH (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstrak. Penelitian ini bertujuan meningkatkan hasil belajar IPA menggunakan media audiovisual pada siswa kelas V Sekolah Dasar Subsidi Usaba Gerai Simpang Dua. Metode penelitian deskriptif, bentuk penelitian tindakan kelas. Kemampuan guru merancang pembelajaran pada siklus I rata-rata skor 2,57 kategori cukup, siklus II rata-rata skor 2,82 kategori cukup, siklus III rata-rata skor 3,43 kategori baik. Kemampuan guru melaksanakan pembelajaran siklus I sebesar 2,02 kategori cukup, siklus II rata-rata skor 2,68 kategori cukup, siklus III rata-rata skor 3,88 kategori baik. Hasil belajar siklus I rata-rata 54,69, siklus II rata-rata 70,63, siklus III sebesar 80,00. Peningkatan perencanaan siklus I ke siklus II sebesar 0,25. Siklus II ke siklus III sebesar 0,61. Peningkatan pelaksanaan siklus I ke siklus II sebesar 0,66, siklus II ke siklus III sebesar 1,2. Peningkatan hasil belajar siklus I ke siklus II sebesar 15,94 siklus II ke siklus III sebesar 9,37. Penggunaan audiovisual dapat meningkatkan pembelajaran IPA Kelas V SD. Kata Kunci : Audio Visual, Hasil Belajar, IPA. Abstract. This research aims to improve the learning outcomes of the science using audiovisual media in class V Elementary School Subsidy Usaba outlets Simpang Dua. The research uses descriptive method, with the form of classroom action research. The results showed that the ability of teachers to design learning in the first cycle an average score of 2.57 category enough, the second cycle an average score of 2.82 category enough, the third cycle an average score of 3.43 both categories. The ability of teachers to implement teaching in the first cycle of 2.02 category enough, the second cycle an average score of 2,68 category enough, the third cycle an average score of 3.88 both categories The first cycle of learning outcomes on average 54.69, the second cycle an average of 70.63, and the third cycle of 80.00. Improved planning of the first cycle to the second cycle of 0.25. The second cycle to the third cycle of 0.61. Improved implementation of the first cycle to the second cycle of 0.66, the second cycle to sikklus III of 1.2. Improving student learning outcomes the first cycle to the second cycle of 15.94 second cycle to the third cycle of 9.37. That can increase the use of audiovisual learning science in Class V SD. Keywords: Audio Visual, Learning Outcomes, IPA.